Cytotoxic T-Lymphocyte Precursor Frequencies in BALB/c Mice after Acute Respiratory Syncytial Virus (RSV) Infection or Immunization with a Formalin-Inactivated RSV Vaccine - Tripp, Ralph A. (American Society for Microbiology, 1998)
A better understanding of the immune response to live and formalin-inactivated respiratory syncytial virus (RSV) is important for developing nonlive vaccines. In this study, major histocompatibility complex (MHC) class I- and II-restricted, RSV-specific cytotoxic T-lymphocyte precursor (CTLp) frequencies were determined in bronchoalveolar lavage (BAL) samples and spleen lymphocytes of BALB/c mice intranasally infected with live RSV or intramuscularly inoculated with formalin-inactivated RSV (FI-RSV). After RSV infection, both class I- and class II-restricted CTLps were detected by day 4 or 5 postinfection (p.i.). Peak CTLp frequencies were detected by day 7 p.i. The class II-restricted CTLp frequencies in the BAL following RSV infection were less than class I-restricted CTLp frequencies through day 14 p.i., during which class I-restricted CTLp frequencies remained elevated, but then declined by 48 days p.i. The frequencies of class II-restricted CTLps in the BAL were 2- to 10-fold less than those of class I-restricted CTLps. For spleen cells, frequencies of both MHC class I- and II-restricted CTLps to live RSV were similar. In contrast, class II-restricted CTLps predominated in FI-RSV-vaccinated mice. RSV challenge of vaccinated mice resulted in an increase in the frequency of class I-restricted CTLps at day 3 p.i. but did not enhance class II-restricted CTLp frequencies. These studies demonstrate differences in the CTLp response to live RSV infection compared with FI-RSV immunization and help define possible mechanisms of enhanced disease after FI-RSV immunization. In addition, these studies provide a quantitative means to address potential vaccine candidates by examining both MHC class I- and II-restricted CTLp frequencies.